Pattern of Anorectal Disorders in Surgical Practice in Rajshahi - Sarkar, H; Hassan, M; Laila, RN (TAJ: Journal of Teachers Association, 2009)
Anorectal disorders include a diverse group of pathological disorders that generate significant patient discomfort and disability. Their prevalence in the general population is probably much higher than that seen in clinical practice, since most patients with symptoms referable to the anorectum do not seek medical attention. Although many anorectal conditions are benign & easily treatable, patients may delay seeking medical advice because of embarrassment or fear of cancer. Both malignant and non malignant conditions often present as advanced disease, requiring more extensive treatment and causing greater patients distress than if conditions had been adequately diagnosed and managed at an earlier stage. This article will highlight predominant symptoms of anorectal conditions and to reveal common anorectal conditions only by D/R/E & proctoscopy. This review will also evaluate current diagnostic and therapeutic methods and establish guidelines for subspecialty referral. In this prospective Study 714 patient with anorectal symptoms were examined, 71.7% were male & 28.29% were female. So male female ratio was M: F=2.5:1. 40.06% patients were within 21-30 years old. The most common symptom was per rectal bleeding (63.59%) & the second common symptom was anal pain (56.16%). The most common anorectal disorder was internal hemorrhoid 60.22% & the second one was anal fissure (50.42%). A large percentage of patients (27.17%) have both hemorrhoid and anal fissure. 98.6% disorders were benign and only 1.4% were malignant. doi: 10.3329/taj.v21i1.3223 TAJ 2008; 21(1): 69-72